Analysis of Factors Influencing Consumer Behavior in Purchasing Products - Otanius Laia (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study aims to determine the factors that influence consumer behavior in purchasing products at the Bintang Keramik Store. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation of owners and consumers. The results of the study indicate that consumer behavior is not only influenced by the products offered, but also by the service experience received during the interaction. Perceptions of product quality also play a significant role in shaping consumer behavior. Consumers assess the product as having good quality, attractive design, This positive perception forms consumer confidence that buying products at Bintang Keramik is able to provide quality products as well as competitive prices and guarantees against damage to goods when purchasing so that consumers feel comfortable and remain loyal in buying products at the store.